Modelling the transient emission from a twin conductor cable. Issue 3 (17th March 2016) - Darney, Ian Brook
Abstract : Using the equations of transmission line theory, a programme is developed to simulate the response of an open‐circuit line to a step pulse. This is compared with the observed response of a twin‐conductor cable. It is deduced that not all of the current delivered to the send conductor arrives back via the return conductor. Some of it departs in the form of radiated emission. A virtual capacitor is used to simulate this, with limited success. However, by adding a second virtual capacitor to simulate transient current being delivered from the return conductor back to the send conductor, a fair correlation is achieved between theoretical and actual results. This analysis demonstrates that the return conductor plays an active role in propagating any signal along the cable. This study also demonstrates that a circuit model can be created to simulate the mechanisms involved in the radiation of interference from power supply cables. This is but one example of the use of circuit models to analyse electromagnetic interference (EMI). The key relationship between electromagnetic theory and circuit theory which enables this technique to be used to analyse any EMI problem is identified. A dramatic simplification in the mathematics can be achieved.